Penyelesaian Sengketa Ekonomi Syariah Ditinjau dari Peraturan Mahkamah Agung Nomor 14 Tahun 2016 dan Hukum Islam - Nurhaliza Faras; Ema Fathimah; Bitoh Purnomo (Universitas Islam Negeri Raden Fatah Palembang, 2023)
The many problems of sharia economic disputes have not all been resolved because the judges who resolve the problems of sharia economic disputes are not special judges who are capable and certified in handling sharia economic disputes. For this reason, this thesis was created to answer this problem, consisting of two problem formulations, namely: What are the Procedures for Settlement of Sharia Economic Disputes in View of Supreme Court Regulation Number 14 of 2016 and Islamic Law? The type of approach method used is qualitative method or literature study whose research uses written data such as books, journals, papers, as well as decisions of the Supreme Court and laws, or from document to document related to this research. From the results of this study it can be concluded that in the settlement of Islamic economic disputes in terms of Perma No. 14 of 2016 it is carried out in two ways, namely simple lawsuits and ordinary lawsuits while in Islam it is carried out by means of peace, arbitration, Al-Qadha.